Sports injuries information for teens : health tips about acute, traumatic, and chronic injuries in adolescent athletes including facts about sprains, fractures, and overuse injuries, treatment, rehabilitation, sport- specific safety guidelines, fitness suggestions, and more - Bellenir, Karen (Detroit, MI : Omnigraphics, 2008)
"Provides basic consumer health information for teens about sports-related injury prevention, treatment, and rehabilitation. Includes index and resource information"--Provided by publisher
Includes bibliographical references and index
Keywords: Sports injuries; Teenagers -- Wounds and injuries -- Prevention; Wounds and injuries